A Study of the Individualism Accounts on American Literature through Reader Response Criticism - Didik Murwantono (Rubikon : Journal of Transnational American Studies, 2022)
This study is by no means a comprehensive account of individualism or more accurately, individualism, in America. It is intended to be more suggestive than comprehensive though it is characterized by more summery than controversy. Many ideas as well as some of the highlights of American manifestations of individualism and modes of individualistic thought and philosophy have been added. What follows, then, is merely a look at some of the high-water marks of literary American individualism and an attempt to offer some cursory explanations for this American phenomenon in theory and practice. This study was under an exploratory qualitative method supported by an interdisciplinary approach of American Studies. Reader-Response criticism is used to make perspective and interpretation without a doubt. The sample was 28 students taking the American Society and literature course at the  Universitas Islam Sultan Agung Semarang. The completion of this research shows the students have creativity and freedom to express their innovation in learning American literature. The cornerstone of individual conscience has to be their credos for changing into a better life through the social, political, economic, and moral autonomy of each individual.